Strategi Guru Dalam Mengintegrasikan Pembelajaran Baca Tulis Al-Qur'an Dengan Program Tahfidzul Qur'an di MTS. Miftahul Ulum Gondang - Nofika Ria Nur Farida; Rizky Dwi Ratna Septinawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Qur'anic education in madrasahs not only emphasizes technical reading skills but also focuses on strengthening memorization and developing Qur'anic character. MTs Miftahul Ulum Gondang implements an integration strategy between Qur'anic Reading and Writing (BTQ) instruction and the Tahfidz al-Qur'an program through collaboration between BTQ and Tahfidz teachers in planning, implementation, and evaluation. This study aims to analyze teachers' strategies in integrating BTQ instruction with the Tahfidz al-Qur'an program and to reveal the implications of these strategies for students' abilities, attitudes, and interest in the Qur'an. This research employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. Research subjects included BTQ teachers, Tahfidz teachers, the school principal, and students. Data were analyzed using the Miles and Huberman model (data reduction, data display, and conclusion drawing), while validity was ensured through source and method  triangulation. The findings indicate that teachers group students into three levels: Awwaliyah, Al-Qur'an, and Tahfidz, with differentiated instruction and methods including talaqqi, tikrar, and sima'an. Continuous and integrated evaluation was employed.